Desenvolvimento de uma plataforma de bioinformática integrada aplicada a identificação molecular de microrganismos patogênicos - Sarmento, Felipe José de Queiroz (2013)
Various researches in molecular epidemiology, molecular diagnosis and evolutionary genetics related to pathogens are compared to managing large amounts of data derived from institutions such as, hospitals or laboratories. Although there already are some proposals to connect molecular information to the diagnosis of pathogens, none of them uses high performance bioinformatics tools which are embedded in a system and linked to a patient’s electronic record. The MolEpi tool has been developed as a system of data and information management addressed to public health, incorporating clinical and epidemiological information about patients, as well as molecular data of 16S rRNA sequences of pathogenic bacteria. In order to confirm which species of these bacteria were identified, biological samples (urine, secretions and purulent wounds, tracheal aspirate and blood) and subsequently incubation and growth of colonies in culture, and PCR was used followed by sequencing and analysis of the conserved coding region for 16S ribosomal RNA (rDNA). Such strategy enabled fast bacterial identification, regardless of prior knowledge of the species of microorganism under study. Moreover MolEpi is a system interconnected to repositories of specific sequences as Genbank (NCBI), RDP-II (Ribosomal Database Project - MSU) and GreenGene (LBL). In this way, once the sequences of clinical isolates are confirmed and validated, they can be used as reference in the identification of other unknown microorganisms. Thus, a local database was established, representing the profile of pathogens found in the hospital unity of study and which should be object of public health surveillance. In order to develop MolEpi, we used the Java programming language and the PostgreSQL8.3 object-relational database. It was also developed BACSearch, which has the following programs to handle the analysis of 16S rDNA sequences, we used the framework BioJava; to multiple alignment, ClustalW2, MAFFT and MUSCLE, and for editing of multiple alignment and phylogenetic analysis, the JalView2.4.0 was used. The system was validated with 200 clinical specimens isolated and identified from sites of nosocomial infection. The DNA sequences produced from these samples were subjected to BLAST by using the developed tool, which identified Pseudomonas aeruginosa, Acinetobacter baumannii, Klebsiella pneumoniae and Morganella morganii as the main pathogens involved. Data on resistance patterns of the species were obtained in microbiology laboratory, and incorporated into the database. The application of MolEpi tool to the Health System can provide prompt and accurate diagnosis, connected to relevant network information which can be intended for health professionals.